Synthesis and hydrolysis of oligodeoxyribonucleotides containing 2-aminopurine. - Fujimoto, J (1996)
A new method is reported for the synthesis of oligodeoxyribonucleotides containing 2-aminopurine residues at selected sites. This method involves protection of the 2-aminopurine ribonucleoside, reduction to the deoxyribonucleoside and standard preparation of the 5'-0- (4,4'-dimethoxytrityl)-3'-O-(2-cyanoethyl)-N,N- diisopropylphosphoramidite. The 2-aminopurine phosphoramidite prepared by this method couples with high efficiency and is stable under standard automated synthesis conditions. The presence and location of the 2-aminopurine residue is easily verified by treatment of the oligodeoxyribonucleotide with hot piperidine. The mechanism for selective hydrolysis of the 2-aminopurine residue in alkaline solution is predominantly direct cleave of the glycosidic bond.